Recovery of Soil Organic Carbon under Different Nutrient Management Practices in Acid Soil of Meghalaya - VERMA, B.C.; CHOUDHURY, B.U.; RAMKRUSHNA, G.I.; KUMAR, MANOJ; BORDOLOI, L.J.; HAZARIKA, S.; RAMESH, T.; BHUYAN, D. (Indian Journal of Hill Farming, 2015)
Soil organic carbon (SOC) is the central element that affects most of the physical, chemical and biological properties of soil. Soil health and quality are very much dependent on these properties; hence SOC is important in maintaining the soil health and quality. Present study was formulated to see the effect of nutrient management practices on two soil carbon fractions and relative recovery of one over the other. Surface soil samples (0-150 mm) were collected from the field of on-going experiment on soil carbon dynamics under different nutrient management practices on acid soil. Processed soil samples were used for subsequent analysis. Total carbon (TC) content varied from 4.75 to 4.91% and 4.96 to 5.14% across the nutrient management practices under maize and groundnut, respectively. In maize, the SOC content varied from 1.25 to 1.90%, however in groundnut, it varied from 1.26 to 1.98%. Recovery of carbon by dichromate method varied from 26.2 to 38.8% in maize and 25.4 to 38.5% in groundnut, respectively. Recovery is more (30-38%) in recently manured plots. Recovery percentage of carbon is significantly affected by the different nutrient management practices. It implies that recovery percentage of carbon is highly variable and varied due to different nutrient management practices. Hence, the conversion factor (SOC to TC) generated for the one soil or for the one region cannot be applicable for the other soil or region. This conversion factor must be specific for a particular soil or for the particular region and must be developed individually.